Which method for the laparoscopic repair of inguinal hernia?; TAPP versus TEP - Akturk, Remzi; Serinsoz, Serdar (Annals of Medical Research, 2021)
Aim: The aim of this study is to prove that the total extraperitoneal patch plasty (TEP) method can be accepted as a standard method in elective and appropriate cases. Materials and Methods: Six hundred sixty-five (665/678) patients with an uncomplicated primary inguinal hernia who consented to participate in the study were randomized into two groups: Group I transabdominal preperitoneal patch plasty (TAPP) repair and Group II TEP repair. Perioperative and postoperative complications and recurrence were detected with the help of radiology unit of our hospital and recorded. The patients were followed up for 1, 6, 12, 24 and 48 weeks.Results: The difference between the number of Tackers and return to work was significant (p0.05). While complications related to bleeding and anaesthesia were more common in TAPP (p0.05). A significant difference was found between the two methods in terms of all complications except for chronic pain, seroma of inguinal area, subcutaneous emphysema and testicular ischemia (p 0.05).Conclusion: It is indisputable that the TEP method is less invasive than TAPP. TAPP should still remain method used in the laparoscopic hernia learning curve for the pushing forward of laparoscopic anatomy vision and used for very complicated inguinal hernias such as the undescended testis and giant inguinal hernias.